Study on the Effect of EICP Combined with Nano-SiO2 and Soil Stabilizer on Improving Loess Surface Strength - Xueyan Wang; Bo Wang; Yili Yuan; Tao Yang; Guojie Dong; Chen Shi (Buildings)
Loess, predominantly distributed in arid and semi-arid regions of central and western China, exhibits low shear strength and structural instability, rendering it prone to geological hazards such as landslides and collapses, which pose significant threats to local infrastructure and safety. This study evaluated the urease activity of soybean and sword bean at different temperatures to screen the optimal enzyme source for enzyme-induced carbonate precipitation (EICP). Methods including single EICP, EICP combined with nano-SiO2, and EICP combined with both nano-SiO2 and soil stabilizer (SS) were adopted to enhance the surface strength of loess. The results showed that the EICP technique significantly improved the surface strength of loess, especially with the addition of nano-SiO2 and soil stabilizer. This study confirmed that using sword bean urease treated at −20 °C for 24 h in combination with 1.5% nano-SiO2 was both cost-effective and efficient in reinforcement. The incorporation of 5% soil stabilizer further enhanced the surface strength, and the accuracy was further verified by combining the results of SEM and XRD. Future research will focus on optimizing the material ratio to maximize the improvement of surface strength, providing an economical and feasible solution for rapid loess solidification, and evaluating the long-term durability under cyclic wet and dry conditions.